2015
DOI: 10.1177/1932296815598776
|View full text |Cite
|
Sign up to set email alerts
|

Basement Membrane-Based Glucose Sensor Coatings Enhance Continuous Glucose Monitoring in Vivo

Abstract: Basement-membrane-based sensor coatings enhance glucose sensor function in vivo, by minimizing or preventing sensor-induced tissues reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…We have also demonstrated that MΦ can act as metabolic sinks for glucose by depleting local glucose levels in vitro and in vivo and causing anomalous glucose sensor reading (Klueh et al 2014a). These and other studies support our general hypotheses that MΦ recruitment and activation can directly decrease glucose sensor function and CGM performance in vivo (Klueh et al 2010a; Klueh et al 2015; Novak and Reichert 2015; Novak et al 2014). Since the recruitment and accumulation of inflammatory leukocytes to injured tissue is dependent on the local generation of leukocyte chemotactic factors (LCF), we chose to investigate the role of monocyte/macrophage LCF in controlling MΦ recruitment into sensor implantation sites and sensor function (Figure 1).…”
Section: Introductionsupporting
confidence: 89%
“…We have also demonstrated that MΦ can act as metabolic sinks for glucose by depleting local glucose levels in vitro and in vivo and causing anomalous glucose sensor reading (Klueh et al 2014a). These and other studies support our general hypotheses that MΦ recruitment and activation can directly decrease glucose sensor function and CGM performance in vivo (Klueh et al 2010a; Klueh et al 2015; Novak and Reichert 2015; Novak et al 2014). Since the recruitment and accumulation of inflammatory leukocytes to injured tissue is dependent on the local generation of leukocyte chemotactic factors (LCF), we chose to investigate the role of monocyte/macrophage LCF in controlling MΦ recruitment into sensor implantation sites and sensor function (Figure 1).…”
Section: Introductionsupporting
confidence: 89%
“…Aseptic techniques were utilized during the coating process and before implantation. To coat the glucose sensors with crosslinked BM, the glucose sensors were placed on a sterile polytetrafluoroethylene (PTFE) liner by modification of our previously described methods . Specifically, 50 μL of dialyzed Cultrex (15 mg protein/mL) was applied on one side of each sensor and placed in a 37°C incubator for 2 h (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Once it was established that sensor coating did not negatively impact sensor performance in vitro , we evaluated the performance of the X‐Cultrex‐coated sensors versus uncoated sensors in our CGM mouse model . Cultrex‐ and X‐Cultrex‐coated and noncoated sensors were implanted in CD‐1 mice (Jackson Laboratory, Bar Harbor, ME) and CGM was undertaken for a period up to 28 days as described previously . Blood glucose reference measurements from the tail vein were obtained over the 28‐day implantation period using Bayer Contour blood glucose monitors.…”
Section: Methodsmentioning
confidence: 99%
“…These include improvements in CGM signal filtering, denoising, and enhancement that resulted in significantly better sensor performance. 9 Furthermore, reduction of biofouling and enzyme degradation can reduce signal error and improve reliability and longevity of CGM, 10,11 as well as standardized and less traumatic sensor insertion. 10 Although a consensus guideline was proposed in 2008, 12 the scientific community has yet to agree upon how to best assess CGM accuracy.…”
Section: -6mentioning
confidence: 99%